Modified PPS fiber filtering material and preparation method thereof

Through the preparation of modified PPS fiber materials and the chemical treatment of modified boron carbide, the problems of easy oxidation and insufficient toughness of polyphenylene sulfide fibers in high temperature environments are solved, and higher oxidation resistance and mechanical properties are achieved. Meets the filter material needs in high temperature and high corrosion environments.

CN119303382AInactive Publication Date: 2025-01-14ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411589969.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyphenylene sulfide fibers are prone to oxidation and cross-linking under high temperature or strong oxidation environments, resulting in poor resistance to oxidants and insufficient toughness, making it difficult to meet the increasingly high requirements of filter materials.

Method used

Using the preparation method of modified PPS fiber filter material, the PPS resin, modified boron carbide and ethylene-octene copolymer are dried and melt blended, extruded and granulated, and spinning, cooling, stretching, and adding The modified PPS fiber filter material was prepared by rolling and heat setting treatment. The modified boron carbide was obtained through a specific chemical reaction to form a stable oxide film to enhance oxidation resistance and mechanical properties.

Benefits of technology

It significantly improves the oxidation resistance, heat resistance and mechanical properties of the filter material, enhances its stability in high temperature and corrosion environments, and meets higher filter material requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125323270000031
    Figure BDA0005125323270000031
  • Figure BDA0005125323270000032
    Figure BDA0005125323270000032
  • Figure BDA0005125323270000041
    Figure BDA0005125323270000041
Patent Text Reader

Abstract

The invention discloses a modified PPS fiber filter material and a preparation method thereof, and belongs to the technical field of filter materials. Comprising the following raw materials in parts by weight: 60-80 parts of PPS resin, 6-18 parts of modified boron carbide and 10-20 parts of an ethylene-octylene copolymer. The filter material prepared by the invention takes polyphenylene sulfide as a matrix, so that the filter material is endowed with excellent strength, high temperature resistance and corrosion resistance; wherein the ethylene-octylene copolymer can improve the toughness of the filter material; wherein the modified boron carbide is good in compatibility with a matrix, the oxidation resistance, the heat resistance and a certain degree of mechanical properties of the filter material can be remarkably enhanced, and the properties are long and stable; therefore, the filter material prepared by the invention is excellent in corrosion resistance, also has stable and efficient oxidation resistance, heat resistance and mechanical properties, and has important application value in the technical field of filter materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of filter materials, and in particular, relates to a modified PPS fiber filter material and a preparation method thereof. Background Art

[0002] In the production process of thermal power generation, steel, cement and other industries, a large amount of dust will be generated, causing serious pollution to the atmosphere. Therefore, the state has formulated strict requirements for the atmospheric emissions of such enterprises, and bag dust removal is a widely used dust removal method.

[0003] In bag-type dust removal, the dust bag plays an important role in the dust removal effect, and the quality of the dust bag depends on the material of the dust bag. Usually, the dust bag is made of polyphenylene sulfide (PPS) fiber. Polyphenylene sulfide is a polymer with a benzene ring connected to sulfur atoms in the para position to form a macromolecular rigid main chain. It has excellent strength, rigidity and fatigue resistance at high temperatures, and has good heat resistance and corrosion resistance. Due to its excellent performance, it is often used as a filter bag in power plants and other places. However, the CS bond energy on the polyphenylene sulfide macromolecular chain is low, and it is easy to break and oxidative cross-link under high temperature or strong oxidizing environment conditions; therefore, polyphenylene sulfide fiber has poor resistance to corrosive gases such as oxidants, especially when facing high-temperature flue gas. When the temperature is higher than the continuous use temperature of the fiber, the basic structure and properties of the fiber will change, and the fiber will be easily deformed and aged. The increase in temperature will accelerate the chemical reaction rate. Not only will the acid gas accelerate the corrosion reaction of the fiber, but the high temperature will also promote the hydrolysis and oxidation reaction of the fiber, resulting in the loss of material performance. Moreover, polyphenylene sulfide is brittle and has poor toughness. Air filter bags made of ordinary polyphenylene sulfide fibers can hardly meet people's increasingly high requirements. Therefore, it is necessary to solve the above problems to meet the higher requirements in the field of filter material technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a modified PPS fiber filter material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing a modified PPS fiber filter material comprises the following steps:

[0007] A1, after drying PPS resin, modified boron carbide and ethylene-octene copolymer (POE), adding them to a high-speed mixer for mixing, then adding them to a high-mixing twin-screw extruder, melt blending, extrusion granulation, vacuum drying, to obtain a modified PPS masterbatch;

[0008] A2. The modified PPS masterbatch is melt-spun, ejected from a spinneret, cooled and solidified, stretched, oiled, rolled, heat-set, cut, and packaged to obtain a modified PPS fiber filter material.

[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 60-80 parts of PPS resin, 6-18 parts of modified boron carbide, and 10-20 parts of ethylene-octene copolymer.

[0010] Furthermore, in step A1, the speed of the high-speed mixer is 800-1000 r / min, and the mixing time is 15-30 min.

[0011] Furthermore, in step A1, the vacuum drying condition is 120-140° C., and the drying time is 6-8 hours.

[0012] With polyphenylene sulfide as the matrix, the filter material is endowed with excellent strength, high temperature resistance and corrosion resistance; the added ethylene-octene copolymer is a polyolefin thermoplastic elastomer with excellent elasticity, high elongation and good low temperature performance, which can improve the toughness of the filter material.

[0013] Furthermore, the modified boron carbide is prepared by the following steps:

[0014] S1. In a three-necked flask equipped with a thermometer, an electromagnetic stirrer and a spherical condenser, a drying tube is added to the outlet of the condenser, and the drying tube is connected to a tail gas absorption device to absorb the generated hydrogen chloride gas. After pentaerythritol and benzene are mixed, phosphorus trichloride is slowly added dropwise under stirring, and the temperature is controlled not to exceed 35° C. After the addition is completed, the temperature is raised to 75° C., and the reaction is refluxed for 4 hours. After the reaction is completed, the solvent benzene and excess phosphorus trichloride are distilled off to obtain intermediate 1; the ratio of pentaerythritol, benzene and phosphorus trichloride is 13.6 g:100 mL:27.4 g;

[0015] Pentaerythritol reacts with phosphorus trichloride to obtain intermediate 1; the specific reaction is as follows:

[0016]

[0017] S2, in a three-necked flask equipped with a stirring device, intermediate 1, pentamethylpiperidinol, potassium carbonate (acid binding agent) and N, N-dimethylformamide (DMF) were mixed and stirred uniformly, the reaction temperature was controlled to 75 ° C, the reaction was kept warm for 6 hours, the reaction was completed, filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (eluent using a mixed solvent of chloroform / acetone, the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, pentamethylpiperidinol, potassium carbonate, and N, N-dimethylformamide was 28.2g:17.1g:15mL:100mL;

[0018] Under the catalysis of potassium carbonate, intermediate 1 reacts with pentamethylpiperidinol, and by controlling the molar ratio of the two to be close to 1:1 and a slight excess of intermediate 1, only one chlorine group on intermediate 1 participates in the reaction to obtain intermediate 2; the specific reaction process is as follows:

[0019]

[0020] S3. In a three-necked flask equipped with a stirring device, the intermediate 2, p-hydroxybenzoic acid, potassium carbonate and N,N-dimethylformamide were mixed and stirred uniformly, the reaction temperature was controlled to 80°C, and the reaction was kept warm for 8 hours. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 4:3), and the eluent was removed by rotary evaporation to obtain a modifier; the ratio of the amount of the intermediate 2, p-hydroxybenzoic acid, potassium carbonate and N,N-dimethylformamide was 39.9 g:13.8 g:15 mL:150 mL;

[0021] Potassium carbonate is used as an acid-binding agent to remove the hydrogen chloride generated by the reaction, and the intermediate 2 undergoes a nucleophilic substitution reaction with p-hydroxybenzoic acid to obtain a modifier. The specific reaction process is shown below:

[0022]

[0023] S4, mix boron carbide and ethanol aqueous solution, add to a magnetic stirring device, add magnet, start stirring, disperse for 30 minutes, make boron carbide evenly dispersed in the ethanol aqueous solution, evacuate the device, pass nitrogen, add γ-aminopropyltriethoxysilane (silane coupling agent KH-550), start heating, set to 50 ° C, stir for 30 minutes, then raise the temperature to 80 ° C, react for 4 hours, the reaction is complete, filter, wash with anhydrous ethanol, and then dry in a vacuum drying oven for 2 hours to obtain pre-modified boron carbide; the ratio of boron carbide, ethanol aqueous solution, and γ-aminopropyltriethoxysilane is 1g:100mL:3.5g;

[0024] There are many -OH groups on the surface of boron carbide, which can introduce -NH2 active groups by reacting with KH-550 to obtain pre-modified boron carbide;

[0025] S5. Ultrasonicate the pre-modified boron carbide in N,N-dimethylformamide for 30 minutes. After uniform dispersion, add the modifier and DCC (dehydrating agent) and mix and stir evenly. Slowly heat to 60°C, use a magnetic stirrer (speed 1000r / min), stir for 4 hours and then stop heating. After the temperature drops to room temperature, filter and take the filter residue, wash it with anhydrous ethanol, dry it, and grind it to obtain modified boron carbide. The ratio of the amount of pre-modified boron carbide, N,N-dimethylformamide, modifier, and DCC is 1g:100mL:7.5g:8.3g.

[0026] The amino group on the pre-modified boron carbide reacts with the carboxyl group on the modifier molecule to undergo an amidation reaction. With the help of a dehydrating agent, the reaction can be carried out under relatively mild conditions to obtain modified boron carbide.

[0027] The structure of boron carbide molecules is quite special, and the chemical reaction between boron carbide and oxidants is relatively slow, which makes boron carbide not easily corroded by oxygen, and boron carbide can form a stable oxide film, which has strong oxidation resistance, heat resistance and certain mechanical properties. By modifying boron carbide, that is, forming an organic layer on its surface, the interfacial compatibility between boron carbide and polyphenylene sulfide matrix can be greatly improved, thereby promoting the uniform dispersion of boron carbide in the matrix, so that the performance of boron carbide can be fully exerted, and the oxidation resistance, heat resistance and mechanical properties of the matrix can be greatly enhanced. In addition, the modified boron carbide is also connected with phosphite, hindered amine and benzene ring structure, among which phosphorous acid As a kind of auxiliary antioxidant, acid esters can decompose hydroperoxides generated in polymers due to oxidative aging, making them inactive substances, thereby achieving the purpose of terminating or delaying the oxidative degradation of polymers; in turn, the introduced hindered amine can act as a light stabilizer. The hindered amine will decompose hydrogen dioxide to produce stable nitroxide free radicals during light protection. This compound can very effectively capture the free radicals generated during photo-oxidative degradation, effectively inhibit the photo-oxidative degradation of the matrix, and can synergize with phosphite and boron carbide to greatly enhance the antioxidant properties of the matrix; finally, the introduced benzene ring can improve the compatibility of modified boron carbide and polyphenylene sulfide to a certain extent;

[0028] It should be noted that boron carbide is an inorganic material. Organic molecular chains are grafted on its surface, making it difficult for them to seep out and migrate, thus ensuring the long-term stability of various properties of the modified boron carbide.

[0029] Beneficial effects of the present invention:

[0030] 1. The filter material prepared by the present invention uses polyphenylene sulfide as a matrix, which gives the filter material excellent strength, high temperature resistance and corrosion resistance;

[0031] 2. The added ethylene-octene copolymer can improve the toughness of the filter material;

[0032] 3. By modifying boron carbide, compared with ordinary boron carbide, it has better compatibility with the matrix, can significantly enhance the oxidation resistance, heat resistance and mechanical properties of the filter material to a certain extent, and the performance is long-term and stable;

[0033] Therefore, the filter material prepared by the present invention has excellent corrosion resistance, stable and efficient oxidation resistance, heat resistance and mechanical properties, and has important application value in the field of filter material technology. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1

[0036] Preparation of modified boron carbide:

[0037] S1. In a three-necked flask equipped with a thermometer, an electromagnetic stirrer and a spherical condenser, a drying tube is added to the outlet of the condenser, and the drying tube is connected to a tail gas absorption device to absorb the generated hydrogen chloride gas. After mixing 13.6 g of pentaerythritol and 100 mL of benzene, 27.4 g of phosphorus trichloride is slowly added dropwise under stirring, and the temperature is controlled not to exceed 35° C. After the addition is completed, the temperature is raised to 75° C., and the reaction is refluxed for 4 hours. After the reaction is completed, the solvent benzene and excess phosphorus trichloride are removed by distillation to obtain intermediate 1;

[0038] S2, in a three-necked flask equipped with a stirring device, 28.2g of intermediate 1, 17.1g of pentamethylpiperidinol, 15mL of potassium carbonate and 100mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 6h. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of chloroform / acetone, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0039] S3, in a three-necked flask equipped with a stirring device, 39.9g of intermediate 2, 13.8g of p-hydroxybenzoic acid, 15mL of potassium carbonate and 150mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 80°C, and the reaction was kept warm for 8h. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 4:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0040] S4, 1g of boron carbide was mixed with 100mL of ethanol aqueous solution, added to a magnetic stirring device, added a magnet, started stirring, dispersed for 30min, so that the boron carbide was evenly dispersed in the ethanol aqueous solution, the device was evacuated, nitrogen was introduced, and then 3.5g of γ-aminopropyltriethoxysilane was added, and heating was started, set to 50°C, stirred for 30min, and then heated to 80°C and reacted for 4h. After the reaction was completed, it was filtered, washed with anhydrous ethanol, and then dried in a vacuum drying oven for 2h to obtain pre-modified boron carbide;

[0041] S5. Ultrasonicate 1 g of pre-modified boron carbide in 100 mL of N,N-dimethylformamide for 30 min. After uniform dispersion, add 7.5 g of modifier and 8.3 g of DCC and mix and stir evenly. Slowly heat to 60 ° C. Use a magnetic stirrer (speed 1000 r / min). Stop heating after stirring for 4 h. After the temperature drops to room temperature, filter, take the filter residue, wash it with anhydrous ethanol, dry it, and grind it to obtain modified boron carbide.

[0042] Embodiment 2

[0043] Preparation of modified boron carbide:

[0044] S1. In a three-necked flask equipped with a thermometer, an electromagnetic stirrer and a spherical condenser, a drying tube is added to the outlet of the condenser, and the drying tube is connected to a tail gas absorption device to absorb the generated hydrogen chloride gas. After mixing 27.2 g of pentaerythritol and 200 mL of benzene, 54.8 g of phosphorus trichloride is slowly added dropwise under stirring, and the temperature is controlled not to exceed 35° C. After the addition is completed, the temperature is raised to 75° C., and the reaction is refluxed for 4 hours. After the reaction is completed, the solvent benzene and excess phosphorus trichloride are removed by distillation to obtain intermediate 1;

[0045] S2, in a three-necked flask equipped with a stirring device, 56.4g of intermediate 1, 34.2g of pentamethylpiperidinol, 30mL of potassium carbonate and 200mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 6h. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of chloroform / acetone, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0046] S3, in a three-necked flask equipped with a stirring device, 79.8g of intermediate 2, 27.6g of p-hydroxybenzoic acid, 30mL of potassium carbonate and 300mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 80°C, and the reaction was kept warm for 8h. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 4:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0047] S4, 2g of boron carbide was mixed with 200mL of ethanol aqueous solution, added to a magnetic stirring device, added a magnet, started stirring, dispersed for 30min, so that the boron carbide was evenly dispersed in the ethanol aqueous solution, the device was evacuated, nitrogen was introduced, and then 7g of γ-aminopropyltriethoxysilane was added, and heating was started, set to 50°C, stirred for 30min, and then the temperature was raised to 80°C, and the reaction was carried out for 4h. After the reaction was completed, the solution was filtered, washed with anhydrous ethanol, and dried in a vacuum drying oven for 2h to obtain pre-modified boron carbide;

[0048] S5. Ultrasonicate 2 g of pre-modified boron carbide in 200 mL of N,N-dimethylformamide for 30 min. After uniform dispersion, add 15 g of modifier and 16.6 g of DCC and mix and stir evenly. Slowly heat to 60 ° C. Use a magnetic stirrer (speed 1000 r / min). Stop heating after stirring for 4 h. After the temperature drops to room temperature, filter, take the filter residue, wash it with anhydrous ethanol, dry it, and grind it to obtain modified boron carbide.

[0049] Embodiment 3

[0050] A1. After drying, 60 g of PPS resin, 6 g of modified boron carbide obtained in Example 1 and 10 g of ethylene-octene copolymer were added to a high-speed mixer (rotating speed of 800 r / min) and mixed for 15 min, then added to a high-mixing twin-screw extruder, melt blended, extruded into granules, and vacuum dried at 120° C. for 6 h to obtain a modified PPS masterbatch;

[0051] A2. The modified PPS masterbatch is melt-spun, ejected from a spinneret, cooled and solidified, stretched, oiled, rolled, heat-set, cut, and packaged to obtain a modified PPS fiber filter material.

[0052] Embodiment 4

[0053] A1, 70g PPS resin, 12g modified boron carbide prepared in Example 2 and 15g ethylene-octene copolymer were dried and added to a high-speed mixer (rotating speed of 900r / min) for mixing for 20min, then added to a high-mixing twin-screw extruder, melt blended, extruded into granules, and vacuum dried at 130°C for 7h to obtain modified PPS masterbatch;

[0054] A2. The modified PPS masterbatch is melt-spun, ejected from a spinneret, cooled and solidified, stretched, oiled, rolled, heat-set, cut, and packaged to obtain a modified PPS fiber filter material.

[0055] Embodiment 5

[0056] A1, 80g PPS resin, 18g modified boron carbide obtained in Example 2 and 20g ethylene-octene copolymer were dried and added to a high-speed mixer (rotating speed of 1000r / min) for mixing for 30min, then added to a high-mixing twin-screw extruder, melt blended, extruded into granules, and vacuum dried at 140°C for 8h to obtain modified PPS masterbatch;

[0057] A2. The modified PPS masterbatch is melt-spun, ejected from a spinneret, cooled and solidified, stretched, oiled, rolled, heat-set, cut, and packaged to obtain a modified PPS fiber filter material.

[0058] Comparative Example 1

[0059] Ordinary boron carbide of the same mass was used to replace the modified boron carbide in Example 5, and the remaining steps were the same as those in Example 5 to obtain a filter material.

[0060] Comparative Example 2

[0061] Commercially available PPS fibers were used.

[0062] Embodiments 3, 4, 5, and comparative examples 1 and 2 were made into corresponding shapes to be tested according to different test standards, and the following performance tests were performed:

[0063] The national standard GB / T 14337-2008 "Test method for tensile properties of chemical staple fibers" was used to measure the breaking strength and breaking elongation;

[0064] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 14 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2 , test the breaking strength of the sample after aging (GB / T 14337-2008), and calculate the change in breaking strength; breaking strength retention rate = breaking strength after test / breaking strength before test × 100%;

[0065] After placing the sample in a constant temperature supply box at 190°C for 24 hours, the thermal shrinkage rate was measured using the YG369S single fiber thermal shrinkage rate tester;

[0066] The measurement results are shown in the following table:

[0067]

[0068] It can be seen from the above table that the filter material prepared in the embodiment of the present invention has higher oxidation resistance, heat resistance and mechanical properties than the control example, and has important application value in the field of filter material technology.

[0069] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0070] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified PPS fiber filter material, characterized in that: The following steps are involved: A1, after drying PPS resin, modified boron carbide and ethylene-octene copolymer, adding them to a high-speed mixer for mixing, then adding them to a high-mixing twin-screw extruder, melt blending, extrusion granulation, vacuum drying, to obtain modified PPS masterbatch; A2. The modified PPS masterbatch is melt-spun, ejected from a spinneret, cooled and solidified, stretched, oiled, rolled, heat-set, cut, and packaged to obtain a modified PPS fiber filter material.

2. The method for preparing a modified PPS fiber filter material according to claim 1, characterized in that: The modified boron carbide is prepared by the following steps: S1. After pentaerythritol and benzene are mixed, phosphorus trichloride is slowly added dropwise under stirring, and the temperature is controlled not to exceed 35° C. After the addition is completed, the temperature is raised to 75° C. and refluxed for 4 hours. After the reaction is completed, distillation is performed to obtain intermediate 1; S2, mixing intermediate 1, pentamethylpiperidinol, potassium carbonate and N,N-dimethylformamide, stirring evenly, keeping warm at 75°C for 6 hours, filtering, rotary evaporation, column chromatography purification, and rotary evaporation to obtain intermediate 2; S3, mixing the intermediate 2, p-hydroxybenzoic acid, potassium carbonate and N,N-dimethylformamide, stirring evenly, keeping the mixture at 80°C for 8 hours, filtering, rotary evaporating, purifying by column chromatography, and rotary evaporating to obtain a modifier; S4, mixing boron carbide with ethanol aqueous solution, adding to a magnetic stirring device, adding magnet, starting stirring, dispersing for 30 minutes, evacuating the device, introducing nitrogen, then adding γ-aminopropyltriethoxysilane, starting heating, setting to 50°C, stirring for 30 minutes, raising the temperature to 80°C, reacting for 4 hours, completing, filtering, washing, and drying to obtain pre-modified boron carbide; S5. The pre-modified boron carbide was ultrasonically treated in N,N-dimethylformamide for 30 minutes. After being evenly dispersed, the modifier and DCC were added and mixed and stirred evenly. After stirring at 60°C for 4 hours, the heating was stopped. After the temperature dropped to room temperature, the filter was filtered, the filter residue was washed, dried, and ground to obtain modified boron carbide.

3. The method for preparing a modified PPS fiber filter material according to claim 2, characterized in that: In step S1, the ratio of pentaerythritol, benzene and phosphorus trichloride is 13.6 g:100 mL:27.4 g.

4. The method for preparing a modified PPS fiber filter material according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, pentamethylpiperidinol, potassium carbonate and N,N-dimethylformamide is 28.2 g:17.1 g:15 mL:100 mL.

5. The method for preparing a modified PPS fiber filter material according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 2, p-hydroxybenzoic acid, potassium carbonate and N,N-dimethylformamide is 39.9 g:13.8 g:15 mL:150 mL.

6. The method for preparing a modified PPS fiber filter material according to claim 2, characterized in that: In step S4, the ratio of boron carbide, ethanol aqueous solution, and γ-aminopropyltriethoxysilane is 1 g:100 mL:3.5 g.

7. The method for preparing a modified PPS fiber filter material according to claim 2, characterized in that: In step S5, the ratio of the amount of pre-modified boron carbide, N,N-dimethylformamide, modifier, and DCC is 1 g:100 mL:7.5 g:8.3 g.

8. The method for preparing a modified PPS fiber filter material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 60-80 parts of PPS resin, 6-18 parts of modified boron carbide, and 10-20 parts of ethylene-octene copolymer.

9. A modified PPS fiber filter material, characterized in that: Prepared according to the method according to any one of claims 1 to 8.

Citation Information

Cited By

  • Ink for printer and preparation method thereof

    CN120349675A

  • Ink for a printer and a method for producing the same

    CN120349675B